Analisis Sentimen Pada Pembelajaran Daring Menggunakan Metode K-Nearest Neightbour - Alfina Novi Yanti; Yuyun Umaidah; Rini Mayasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Corona Virus Disease-2019 has been rampant throughout the world, including in Indonesia. Covid-19 has greatly affected several sectors, one of which is the education sector. The Indonesian government itself implements a policy of courageous learning or distance learning which is carried out from their respective homes. SMA Negeri 3 Cikampek is one of the schools that implements bold learning, this bold learning affects the achievement of learning outcomes. Various students from this bold learning, there are those who agree that this bold learning has an effect on the achievement of learning outcomes and some even give a response that does not agree because it has no effect. For this reason, data mining is applied, especially text mining with the K-Nearest Neighbor algorithm to analyze various student responses to bold learning. The data used is a questionnaire data as much as 592 data. Before the data mining stage, the data is divided into 80% of the training data and 20% of the testing data. The classification with K-Nearest Neighbor quality is 85.35% accuracy, 81.19% precision, 92.42% recall and Auc is 0.902. Based on the quantity of negative classes which are more than positive classes, it is known that students will not agree to bold learning because it affects the achievement of learning outcomes. Keyword: Text mining, Online Learning , Covid-19, K-Nearest Neightbour.